Botryomycosis Due to Staphylococcus Aureus-A Case Report - Manjula A.Vagarali; Shankar G.Karadesai; Sumati A. Hogade (Al Ameen Medical College, 2012)
Objectives: To study Staphylococcus aureus as the causative organism of botryomycosis. Background: the botryomycosis is a chronic purulent granulomatous lesion of the skin, subcutaneous tissue and visceral organs caused by several bacterial species. This condition clinically and histopathologically resembles with that of mycetoma and Actinomycosis. Method: A 51 year old male presented to us with swelling over medial aspect of the right foot with multiple sinuses. He gave a history of trauma 3 years back at the same site. The sample was examined directly by KOH preparation and grams stain. The culture was put up on blood, chocolate, lowenstein Jensen (LJ) and sabouraud dextrose agar (SDA) media. Fungal culture was negative. Result: Staphylococcus aureus was isolated in aerobic culture. Conclusion: the patient with botryomycosis caused by Staphylococcus aureus was subsequently treated with antibiotics and he recovered completely.